Join the IDNLearn.com community and start exploring a world of knowledge today. Ask anything and receive thorough, reliable answers from our community of experienced professionals.
Sagot :
Answer:
B. -6
Step-by-step explanation:
Average rate of change = [tex] \frac{f(b) - f(a)}{b - a} [/tex]
Where,
b = 4, f(b) = -15
a = 2, f(a) = -3
Plug in the values
[tex] \frac{-15 - (-3)}{4 - 2} [/tex]
[tex] = \frac{-12}{2} = -6 [/tex]
The average rate of change of the given quadratic function in the given interval is -6.
How to get the average rate of change?
On the graph, we can see that:
f(4) = -15
f(2) = -3
Then the average rate of change on that interval will be:
[tex]y = \frac{f(4) - f(2)}{4 - 2} = \frac{-15 + 3}{2} = -6[/tex]
Then we conclude that the average rate of change of the given quadratic function on the given interval is -6.
If you want to learn more about rates of change:
https://brainly.com/question/8728504
#SPJ5
Thank you for using this platform to share and learn. Don't hesitate to keep asking and answering. We value every contribution you make. Your search for answers ends at IDNLearn.com. Thank you for visiting, and we hope to assist you again soon.